Fermi-LAT realtime follow-ups of high-energy neutrino alerts - Garrappa S.; Buson S.; Franckowiak A.; Giroletti M.; Liodakis I.; Nanci C.; Fermi-LAT Collaboration (Italy, 2023)
The detection of the flaring gamma-ray blazar TXS 0506+056 in spatial and temporal coincidence with the high-energy neutrino IC-170922A represents a milestone for multi-messenger astronomy. The prompt multi-wavelength coverage from several ground- and space-based facilities of this special event was enabled thanks to the key role of the Fermi-Large Area Telescope (LAT), continuously monitoring the gamma-ray sky. Exceptional variable and transient events, such as bright gamma-ray flares of blazars, are regularly reported to the whole astronomical community to enable prompt multi-wavelength observations of the astrophysical sources. As soon as realtime IceCube high-energy neutrino event alerts are received, the relevant positions are searched, at multiple timescales, for gamma-ray activity from known sources and newly detected emitters positionally consistent with the neutrino localization.
In this contribution, we present an overview of follow-up activities and strategies for the realtime neutrino alerts with the Fermi-LAT, focusing on some interesting coincidences observed with gamma-ray sources. We will also discuss future plans and improvements in the strategies for the identification of gamma-ray counterparts of single high-energy neutrinos.
37th International Cosmic Ray Conference (ICRC2021)